Craftsmen Versus Designers: The difference of in-depth cognitive levels at the early stage of idea generation - Deny Willy Junaidy; Yukari Nagai; Muhammad Ihsan (2016)
This paper investigates the in-depth cognitive levels at the early stage of idea generation for craftsmen and designers. Examining this early stage may explain the fundamental thoughts in observing and defining design problems. We conducted an experiment using think-aloud protocol, where verbalized thoughts were analyzed using a concept network method based on Associative Concept Network Analysis (ACNA). Furthermore, we identified semantic relationships based on Factor Analysis. The findings showed that craftsmen tended to activate low-weighted associative concepts at in-depth cognitive level with a smaller number of polysemous features, thus explaining their concerns about tangible-related issues, such as proportion and shape. Designers, however, activated highly weighted associative concepts with more polysemous features, and they were typically concerned with intangible issues, such as surroundings context (i.e., eating culture) and users’ affective preferences (i.e., companion, appeal).